2020
DOI: 10.1093/mnras/staa3868
|View full text |Cite
|
Sign up to set email alerts
|

The Swift bulge survey: motivation, strategy, and first X-ray results

Abstract: Very faint X-ray transients (VFXTs) are X-ray transients with peak X-ray luminosities (LX) of L$_X \lesssim 10^{36}$ erg s−1, which are not well understood. We carried out a survey of 16 deg2 of the Galactic Bulge with the Swift Observatory, using short (60 s) exposures, and returning every 2 weeks for 19 epochs in 2017–18 (with a gap from 2017 November to 2018 February, when the Bulge was in sun-constraint). Our main goal was to detect and study VFXT behaviour in the Galactic Bulge across various classes of X… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 183 publications
1
26
0
Order By: Relevance
“…The transient X-ray source Swift J0243.6+6124 was discovered on 2017 October 3 by Swift/BAT telescope, and it was suggested that the compact object is a neutron star (Kennea et al 2017). X-ray pulsations were also detected with a period of ∼9.86 s (Bahramian et al 2017;Jenke & Wilson-Hodge 2017;Kennea et al 2017) modulated by the motion in an eccentric orbit (e∼0.1) with a period of ∼28 days (Ge et al 2017;Doroshenko et al 2018). Based on the observation from the 1.3 m telescope of the Skinakas Observatory, the optical counterpart of the source has been identified as a Be star (Kouroubatzakis et al 2017), thus confirming the system as a Be/X-ray binary (BeXRB).…”
Section: Introductionmentioning
confidence: 95%
“…The transient X-ray source Swift J0243.6+6124 was discovered on 2017 October 3 by Swift/BAT telescope, and it was suggested that the compact object is a neutron star (Kennea et al 2017). X-ray pulsations were also detected with a period of ∼9.86 s (Bahramian et al 2017;Jenke & Wilson-Hodge 2017;Kennea et al 2017) modulated by the motion in an eccentric orbit (e∼0.1) with a period of ∼28 days (Ge et al 2017;Doroshenko et al 2018). Based on the observation from the 1.3 m telescope of the Skinakas Observatory, the optical counterpart of the source has been identified as a Be star (Kouroubatzakis et al 2017), thus confirming the system as a Be/X-ray binary (BeXRB).…”
Section: Introductionmentioning
confidence: 95%
“…This luminosity increase is larger than what we see in the light-curve data, which we infer as a larger absorption during the outburst state. It is worth noting that the Swift Bulge Survey did not detect any outburst from CXB3, which in combination with our observations suggests a relatively low duty cycle in the system (Bahramian et al 2021). We also attempted a search for periodicities in the light-curve data but did not detect any significant periods.…”
Section: I G H T C U Rv E Smentioning
confidence: 66%
“…of CXB3, indicate that our assumption of 8 kpc is more likely to be an underestimate than an overestimate. We have also examined Gaia DR2 and EDR3 and concluded that with the large uncertainties in the parallax and inconsistencies between DR2 and EDR3 the data sets are inconclusive at this time, although they are consistent with CXB3 not being a nearby object (Gaia Collaboration 2016, 2021.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of the Very faint X-ray transients (VFXTs [173]), events with peak luminosities < 10 36 erg s −1 is still unknown. Although some have been associated to NS or BH low-mass X-ray binaries or symbiotic systems, the nature of most VFXTs is still uncertain [174]. Current data suggest that they have very low mass-transfer rates, pointing towards the later (or unusual) stages in X-ray binary evolution [175,176].…”
Section: Very Faint X-ray Transientsmentioning
confidence: 99%